Q: What is 9x plus 3x plus 8 plus 1 in simplest form?

Write your answer...

3X^2 + 9X/3X factor out 3X 3X(X + 3)/3X 3X/3X = 1, so... X + 3 is the simplest form here

102 +9x +4 = 9x + 106, which is in its simplest form.

-3x+9x can be simplified to 6x

No. It is 9x, which is a monomial.

9x + 32

9x + 3x - 9x = 6 + 8x - 113x = 8x - 11-5x = -11x = 2.2 or 11/5

x+5+3x-7+9x+3-4x Collect like terms: 9x+1

3x2 + 9x 3x(x + 3) -------------

9x+3y = 6 3y = -9x+6 y = -3x+2 which is now in slope-intercept form

3(x2 + 3x + 1)

9x+3

3x+21x+9x=33x. Break it apart. The factor of x is x and the factors of 33 are 3 and 11. Therefore, the factors of 3x+21x+9x are 3, 11, and x.

3x + 6x +1 = 10 9x = 10 - 1 9x = 9 x = 1

3x + 6y + 6x = 9x + 6y which can be factorised as 3(3x +2y)

Let the symbol ^ mean "to the power" Then 9x^2 + 24x + 16 = (3x + 4)(3x +4) = (3x + 4)^2

(9x + 12) / 3 = 3x+4 ■

9x2 + 9x - 10 =(3x - 2)(3x + 5)

3 / 9x+63 / 3(3x+2)1 / 3x+2

6x + 9x^3 = 3x*(2 + 3x^2)

12

12x + 131 = 189 + 3x 12x - 3x + 131 - 189 = 0 9x - 58 = 0 9x = 58 x = 6,44444

Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x

3x. 15x - 9x = 6x 9x - 6x = 3x 6x - 3x = 3x 3x - 3x = 0

6x+11=92-3x +3x +3x 9x+11=92 -11 -11 9x=81 divide by 9 x=9

-4